New discussion on nonlocal controllability for fractional evolution system of order 1 < r < 2 $1 < r < 2$ - M. Mohan Raja; Velusamy Vijayakumar; Anurag Shukla; Kottakkaran Sooppy Nisar; Shahram Rezapour (Advances in Difference Equations, 2021)
Abstract In this manuscript, we deal with the nonlocal controllability results for the fractional evolution system of 1 < r < 2 $1< r<2$ in a Banach space. The main results of this article are tested by using fractional calculations, the measure of noncompactness, cosine families, Mainardi’s Wright-type function, and fixed point techniques. First, we investigate the controllability results of a mild solution for the fractional evolution system with nonlocal conditions using the Mönch fixed point theorem. Furthermore, we develop the nonlocal controllability results for fractional integrodifferential evolution system by applying the Banach fixed point theorem. Finally, an application is presented for drawing the theory of the main results.